Distinct element modeling of the in-plane and out-of-plane response of ordinary and innovative masonry infill walls. (April 2023) - Chen, Zhangyan; Zhou, Yun; Kinoshita, Takuya; DeJong, Matthew J.
Abstract: Masonry infill walls (MIWs) are essential partition components that are often damaged during earthquakes because of their brittle nature. As a result, innovative solutions are attractive to improve performance of MIWs by reducing damage during in-plane drift or increasing damping. Examples of innovative solutions have been investigated experimentally, but mesoscale or microscale numerical modelling techniques could also be useful to evaluate performance and investigate the principal failure mechanisms of both ordinary and innovative MIWs, and subsequently optimize their design. This paper employs the Distinct Element Method (DEM) to predict the in-plane (IP) and out-of-plane (OOP) response of ordinary and innovative MIWs within RC frames. The DEM methodology used in this study account for the crushing of concrete and masonry, the shear-compression behavior of mortar and the shear behavior of a novel damping layer joint (DLJ) inserted in the MIW (named damped masonry infilled wall (DMIW)). DEM results are compared against experimental results for both MIWs and DMIWs. Two IP and four OOP experimental tests were simulated in total. The DEM simulation methodology is capable of predicting the IP and OOP load–displacement response as well as the damage patterns of the ordinary MIWs and DMIWs, although the local displacement mechanism at the DLJ locations of the DMIW varied for the OOP tests. Local stress distribution differences, as well as modeling modifications for simulating the damage pattern of DMIWs, are further discussed. Overall, the effectiveness of the DEM simulation provides confidence that it could be used to improve upon the DMIW design in the simulation environment.